2015
DOI: 10.1371/journal.pone.0116343
|View full text |Cite|
|
Sign up to set email alerts
|

Temporal-Spatial Correlation between Angiogenesis and Corticogenesis in the Developing Chick Optic Tectum

Abstract: The developing chick optic tectum is a widely used model of corticogenesis and angiogenesis. Cell behaviors involved in corticogenesis and angiogenesis share several regulatory mechanisms. In this way the 3D organizations of both systems adapt to each other. The consensus about the temporally and spatially organized progression of the optic tectum corticogenesis contrasts with the discrepancies about the spatial organization of its vascular bed as a function of the time. In order to find out spatial and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(35 reference statements)
1
2
0
Order By: Relevance
“…However, SEZ NSCs can influence the function of BVs, for example, the blood flow (Lacar et al, 2012b ), and oligodendrocyte progenitors can control angiogenesis through hypoxia-inducible factors (Yuen et al, 2014 ). These are in concert with evidence that embryonic cortical NSCs are important for the establishment of the developing vasculature (Gerhardt et al, 2004 ; Ma et al, 2013 ) and that in many cases vascularization tightly follows the maturation of the nervous system (Rodriguez Celin et al, 2015 ). Recently published work with human NSCs also showed that they provide the necessary juxtacrine and paracrine signals to drive human endothelial cells to form “vasculature-like structures” (Chou et al, 2014 ) and promote angiogenesis in the rodent brain (Hicks et al, 2013 ).…”
Section: Coupling Of Neurogenesis and Angiogenesis; Who Needs Whom?supporting
confidence: 64%
See 2 more Smart Citations
“…However, SEZ NSCs can influence the function of BVs, for example, the blood flow (Lacar et al, 2012b ), and oligodendrocyte progenitors can control angiogenesis through hypoxia-inducible factors (Yuen et al, 2014 ). These are in concert with evidence that embryonic cortical NSCs are important for the establishment of the developing vasculature (Gerhardt et al, 2004 ; Ma et al, 2013 ) and that in many cases vascularization tightly follows the maturation of the nervous system (Rodriguez Celin et al, 2015 ). Recently published work with human NSCs also showed that they provide the necessary juxtacrine and paracrine signals to drive human endothelial cells to form “vasculature-like structures” (Chou et al, 2014 ) and promote angiogenesis in the rodent brain (Hicks et al, 2013 ).…”
Section: Coupling Of Neurogenesis and Angiogenesis; Who Needs Whom?supporting
confidence: 64%
“…As soon as NSCs become specified the processes of self-renewal and expansion are initiated. Low levels of proliferation, adequate for the generation of single neurons and glia and for the construction of primitive neuronal networks and of the early neural tube, can occur in the absence of vascularization (Rodriguez Celin et al, 2015 ). The emergence of larger and more complicated nervous systems required higher levels of proliferation in embryonic neural stem and progenitor cells, and this was partly achieved through their diversification.…”
Section: The Role Of the Vasculaturementioning
confidence: 99%
See 1 more Smart Citation